Mandibular molar root and pulp cavity morphology in Homo naledi and other Plio-Pleistocene hominins. Issue 130 (May 2019) - Kupczik, Kornelius; Delezene, Lucas K.; Skinner, Matthew M.
Abstract: The craniomandibular morphology of Homo naledi shows variable resemblances with species across Homo, which confounds an easy assessment of its phylogenetic position. In terms of skull shape, H. naledi has its closest affinities with Homo erectus, while mandibular shape places it closer to early Homo . From a tooth crown perspective, the smaller molars of H . naledi make it distinct from early Homo and H. erectus . Here, we compare the mandibular molar root morphology of six H. naledi individuals from the Dinaledi Chamber to those of African and Eurasian Plio-Pleistocene fossil hominins (totalling 183 mandibular first, second and third molars). The analysis of five root metric variables (cervical plane area, root length, root cervix volume, root branch volume, and root surface area) derived from microCT reconstructions reveals that the molar roots of H. naledi are smaller than those of Homo habilis, Homo rudolfensis, and H. erectus, but that they resemble those of three Homo sp. specimens from Swartkrans and Koobi Fora in size and overall appearance. Moreover, though H. naledi molar roots are similar in absolute size to Pleistocene Homo sapiens, they differ from H. sapiens in having a larger root volume for a given cervical plane area and less taurodont roots; the root cervix-to-branch proportions of H. naledi are comparable to those of Australopithecus africanus and species of Paranthropus . H. naledi also shares a metameric root volume pattern (M2 > M3 > M1 ) with Australopithecus and Paranthropus but not with any of the other Homo species (M2 > M1 > M3 ). Our findings therefore concur with previous studies that found that H. naledi shares plesiomorphic features with early Homo, Australopithecus, and Paranthropus . While absolute molar root size aligns H. naledi with Homo from North and South Africa, it is distinguishable from these in terms of root volumetric proportions.